The making of a music city : rock and pop in Melbourne - Homan, Shane; Strong, Catherine; Tebbutt, John; Tebbutt, John (London [England] : Bloomsbury Academic, 2021)
"How did Melbourne earn its place as one of the world's 'music cities'? Beginning with the arrival of rock 'n' roll in the 1950s, this book explores the development of different sectors of Melbourne's popular music ecosystem in parallel with broader population, urban planning and media industry changes in the city. The authors draw on interviews with Melbourne musicians, venue owners and policy-makers, documenting their ambitions and experiences across different periods, with accompanying spotlights on the gendered, multicultural and indigenous contexts of playing and recording in Melbourne. Focusing on pop and rock, this is the first book to provide an extensive historical lens of popular music within an urban cultural economy that in turn investigates the contemporary nature and challenges of urban music activities and policy."--
1. Introduction -- 2. The Live Music City -- 3. The Permissive City -- 4. The Media City -- 5. The Recording City -- 6. The Legendary City -- 7. The Branded City -- 8. Conclusion: the Music City.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Popular music -- Australia -- Melbourne (Vic.) -- History; Rock music -- Australia -- Melbourne (Vic.) -- History; Sound recording industry -- Australia -- Melbourne (Vic.); Rock & Pop music; Electronic books